A Bridge between Laparoscopic and Open Technique in Treatment of Pediatricpelvi-Ureteric Junction Obstruction for the Beginners: Laparoscopic Assisted Pyeloplasty in Pediatric Patients - Kalavant, Akshay; Annigeri, Venkatesh (Iranian Journal of Pediatric Surgery, 2022)
Introduction: Laparoscopic pyeloplasty is considered one of the most challenging procedures in the paediatric urology. Long operating time and steep learning curve are drawbacks of the technique. The aim of this study is to assess the feasibility of laparoscopy-assisted pyeloplasty and its outcome. Materials and Methods: It's a retrospective comparative study of patient undergoing pyeloplasty in Shri Dharmasthala Manjunatheshwara(SDM) College of Medical Sciences since June 2018 !ll February 2020. The pa!ents were divided into two groups based on whether patients have undergone laparoscopy-assisted approach (group A) or open pyeloplasty (group B) and both groups were followed up for one year. Laparoscopy-assisted approach constituted of laparoscopic mobilization of pelvi-ureteric junction (PUJ) followed by hand-sewn anastomosis after exteriorising the PUJ. Results: There were 12 patients in group A and 16 patients in group B. Duration of surgery was longer in group A. There were 4 pa!ents in group A, older than 3 years who needed conversion to open surgery. One patient had recurrence of PUJO needing re-do surgery. There was no major complication in open technique except wound infection which required extended hospital stay up to 8 days. There were no significant differences between the two groups in analgesic usage. Conclusion: Laparoscopy-assisted pyeloplasty is an intermediate path for surgeons with less experience in advanced laparoscopy. The reasonable small incision without compromising outcome in ureteropelvic anastomosis is the major advantage of this technique. The procedure is useful in infants but not suitable for the age group of above 3 years.